Halal Certification Literacy for MSME Enterprises 'Aisyiyah Tranting Market Sipirok - Novitasari, Wiwik; Samosir, Benny Sofyan; Habibi, Habibi; Harahap, Erlina (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2024)
MSME business actors have a significant role in the Indonesian economy. However, there are still various obstacles faced by MSME business actors, including those related to halal certification literacy. Based on data from the Halal Product Guarantee Organizing Agency (BPJPH), only around 2.8% of MSMEs in Indonesia have been halal certified. The low level of halal certification among MSMEs is caused by a lack of understanding and literacy regarding the procedures and benefits of halal certification. Sipirok Market is one of the traditional markets in Indonesia with the majority of traders selling various food and beverage products, but the majority do not have halal certification. Therefore, it is important to carry out halal certification literacy activities aimed at MSMEs in 'Aisyiyah Branch of Sipirok Market. Data collection was carried out through focus group discussions, observations and questionnaires. Based on an initial survey conducted on 25 MSMEs at Sipirok Market, it was discovered that as many as 18 MSMEs (72%) had not received halal certification from BPJPH. They generally still do not understand the procedures and requirements needed to obtain halal certification. Apart from that, they also don't know the benefits that can be obtained by having halal certification for the products they sell. Based on the results of community service activities, it can be concluded that halal certification literacy for MSME business actors in the Sipirok Market Branch is still relatively low.